Low skeletal muscle mass in cholangiocarcinoma treated by surgical resection. A meta-analysis. Issue 7 (July 2022) - Surov, Alexey; Pech, Maciej; Omari, Jazan; Melekh, Bohdan; March, Christine; Perrakis, Aristotelis; Wienke, Andreas
Abstract: Background: To date, the role of low skeletal muscle mass (LSMM) in cholangiocarcinoma (CC) is unclear. Our purpose was to analyze the influence of LSMM on survival in patients with CC treated by surgical resection. Methods: MEDLINE, Cochrane, and SCOPUS databases were screened for associations between LSMM and survival in CC up to June 2021. Overall, 16 studies met the inclusion criteria. The methodological quality of the involved studies was analyzed using the QUADAS instrument. The meta-analysis was undertaken using RevMan 5.4 software. Results: The prevalence of LSMM was 48.40%. LSMM was associated with lower overall survival (OS): HR = 2.44, 95%CI = (2.01–2.96) (simple regression); HR = 2.39, 95%CI = (1.83–3.13) (multiple regression). In extrahepatic CC, sarcopenic patients had lower OS, simple regression: HR = 2.11, 95%CI = (1.39–3.20); multiple regression: HR = 2.28, 95%CI = (1.41–3.70). In intrahepatic CC, LSMM predicted recurrence free survival: HR = 2.33, 95%CI = (1.93–2.81) (simple regression); HR = 2.23, 95%CI = (1.73–2.88) (multiple regression). LSMM predicted OS in intrahepatic CC, simple regression: HR = 2.69, 95%CI = (2.24–3.24); multiple regression: HR = 2.43, 95%CI = (1.73–3.41). Conclusion: LSMM is a risk factor for OS in patients with CC treated by surgical resection. LSMM is a predictor of RFS in patients with intrahepatic CC.